Integration concepts in German cities: How can they contribute to Shared Societies?. (12th November 2021) - Hussak, Melanie; Zeigermann, Ulrike; Schilling, Janpeter; Reiter, Anna
Abstract: Integration concepts at the municipal level can be seen as an important step towards a Shared Society. The concept of Shared Society was developed against the background of increasing political and social polarization. A Shared Society means a stable and safe society where everybody feels at home and respected and has equal opportunities. Tolerance and diversity are key elements. This paper analyzes integration concepts of five German cities: Aachen, Frankfurt, Potsdam, Trier and Wiesbaden. It examines their strategies and explores how they could overcome previous assimilative approaches and contribute to a Shared Society. The comparative analysis is based on three key dimensions of a Shared Society: social cohesion, joint structures and enabling environment. We show how the application of the Shared Society concept could address current challenges in the field of migration and integration and discuss factors that drive Shared Society policies and practices in cities.